2018
DOI: 10.18535/ijsrm/v6i7.em07
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Smallholder Farmers Adoption of Eucalyptus Woodlot in Wogera District, North Gondar Zone, Amhara Regional State of Ethiopia

Abstract: Eucalyptus is familiar specious in various weather conditions of the world. Eucalyptus woodlot planation in wogera district become increased since 1970. The study was to examine the determinant factors for the adoption of eucalyptus woodlots by smallholder farmers in Wogera district. Three stage sampling procedure was used to select 118 sample respondent farmers from three purposively selected Kebeles of the district. Household survey was used to collect quantitative data. Econometric model (binary logit model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…The results demonstrated that smallholder farmers with small pieces of land had fewer commercial trees and fruit trees on their farms. These findings are consistent with the findings by Ashraf et al (2015); Danquah (2015); Derbe et al (2018) who found that land size has a positive influence on tree growing by farmers. This is however in conflict with the findings by Owooh (2013) who found out that farmers adopt agroforestry practices to mitigate challenges of land use in small farms.…”
Section: Land Sizesupporting
confidence: 93%
“…The results demonstrated that smallholder farmers with small pieces of land had fewer commercial trees and fruit trees on their farms. These findings are consistent with the findings by Ashraf et al (2015); Danquah (2015); Derbe et al (2018) who found that land size has a positive influence on tree growing by farmers. This is however in conflict with the findings by Owooh (2013) who found out that farmers adopt agroforestry practices to mitigate challenges of land use in small farms.…”
Section: Land Sizesupporting
confidence: 93%
“…Likewise, Jagger et al (2005) also reported that farm woodlots contribute positively to the income and resilience of rural households. Moreover, Gizachew (2017) and Derbe et al (2018) revealed that total land holding of the household heads had significant positive effects on the household's decision to produce and establish Eucalypts woodlot on the farm lands.…”
Section: Ols Model Results Of Determinants Of Commercial Value Of Woodmentioning
confidence: 99%
“…The rainy months extend from June until the end of September. However, most of the persistence rainfall is received during the months of July and August (Derbe et al 2018). According to the district agricultural office (2016) the district has total area coverage of 182,126 ha with cultivated land (46.1%) being the dominant land use followed by, grazing land (22.7%), forest land (11%), building (4.42%), rivers and gorges (2.73%) and others (12.85%).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Related studies (Edesa, 2021) found a positive contribution of farm woodlots to the income of rural households. In addition, other studies (Gizachew, 2017;Gizachew, 2017;Derbe, 2018) indicated that the total land holding size of the local households had significant and positive effects on the income derived from Eucalypts woodlot of their farmlands. The result further agreed with related studies that found that landholding size had a positive relationship with the income derived from woodlot products (Dessie et al, 2019;Asefa, 2021).…”
Section: Determinants Of Income Derived From Eucalyptus Woodlot Using...mentioning
confidence: 96%